Flouting Gricean Maxims for a Laugh: Conversational Implicature and Multimodal Humor Construction in Indonesian Internet Memes - Vera Magria; Rini Afrilesa (Jurnal Ilmiah Langue and Parole, 2026)
This research examines conversational implicature as the mechanism that generates humor in Indonesian internet memes, building on Grice's (1975) Cooperative Principle and its later development by Levinson (1983) and Yule (1996). A meme is treated here not as a static picture-and-caption object but as a compressed communicative event, in which a sender addresses an unseen audience that must reason past the literal surface of an image or caption to recover what is actually intended. Seven Indonesian memes circulating between January 2023 and March 2025 were purposively selected and analyzed through Grice's maxims in combination with Attardo and Raskin's (1991) General Theory of Verbal Humor. Three patterns emerged. Flouting of the maxim of Quality was the most frequent, generally achieved through irony or through the inversion of a familiar proverb or piece of self-help wisdom, and it tended to recast an institutional or personal grievance as a joke. Flouting of the maxim of Relation was rarer but produced sharper comic incongruity, since the humor turned on a single expression carrying two unrelated referents at once; closer inspection suggests this device is better described as an ambiguity rooted in the maxim of Manner that only surfaces as an apparent breach of Relation. A third pattern, termed multimodal flouting in this study, involved memes whose flouted claim was never composed as a caption at all but was already present in a photograph, a sign, or a mural — in one case apparently completed by the audience rather than intended by whoever made the image. This last pattern suggests that Grice's originally speaker-centered account needs to be extended, in digital settings, to cover implicature that is inferred collectively rather than encoded deliberately, and that recovering any of these implicatures depends more on shared Indonesian cultural knowledge than on pragmatic competence of a general or universal kind. This research examines conversational implicature as the mechanism that generates humor in Indonesian internet memes, building on Grice's (1975) Cooperative Principle and its later development by Levinson (1983) and Yule (1996). A meme is treated here not as a static picture-and-caption object but as a compressed communicative event, in which a sender addresses an unseen audience that must reason past the literal surface of an image or caption to recover what is actually intended. Seven Indonesian memes circulating between January - july 2026 were purposively selected and analyzed through Grice's maxims in combination with Attardo and Raskin's (1991) General Theory of Verbal Humor. Three patterns emerged. Flouting of the maxim of Quality was the most frequent, generally achieved through irony or through the inversion of a familiar proverb or piece of self-help wisdom, and it tended to recast an institutional or personal grievance as a joke. Flouting of the maxim of Relation was rarer but produced sharper comic incongruity, since the humor turned on a single expression carrying two unrelated referents at once; closer inspection suggests this device is better described as an ambiguity rooted in the maxim of Manner that only surfaces as an apparent breach of Relation. A third pattern, termed multimodal flouting in this study, involved memes whose flouted claim was never composed as a caption at all but was already present in a photograph, a sign, or a mural — in one case apparently completed by the audience rather than intended by whoever made the image. This last pattern suggests that Grice's originally speaker-centered account needs to be extended, in digital settings, to cover implicature that is inferred collectively rather than encoded deliberately, and that recovering any of these implicatures depends more on shared Indonesian cultural knowledge than on pragmatic competence of a general or universal kind.